2010
DOI: 10.1111/j.1365-2605.2009.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity of the testis and PKG I / StAR interaction regulate the Leydig cell adaptive response to repeated immobilization stress

Abstract: The role of the structural complexity of the testis and the nitric oxide (NO)-cyclic guanosine monophosphate (cGMP) signalling pathway was analysed in adult male rats exposed to acute and repeated immobilization stress (IMO). In whole testis preparations, exposure to acute and repeated IMO caused an increase in NO production. In contrast, NO production was inhibited in interstitial cell preparations after exposure to all types of stress. In purified Leydig cell preparations, NO production was inhibited only af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 70 publications
(159 reference statements)
2
66
0
Order By: Relevance
“…The proportion of Leydig cells present in culture was determined by staining for HSD3B activity (Payne et al, 1980), and was found to be 95.3 ± 2.7%, while the viability was more than 90%. The steroidogenic capacity of Leydig cells (estimated by dose-dependent stimulation with hCG) and the activity of steroidogenic enzymes (estimated by incubating cells with increasing concentrations of steroid substrates), were in line with those previously published by others (Akinbami et al, 1994) as well as our group (Andric et al, 2007(Andric et al, , 2010aKostic et al, 2008Kostic et al, , 2010Kostic et al, , 2011. These data were not showed and served to us just as internal control.…”
Section: Extraction Of Steroids From Testicular Tissuesupporting
confidence: 88%
See 4 more Smart Citations
“…The proportion of Leydig cells present in culture was determined by staining for HSD3B activity (Payne et al, 1980), and was found to be 95.3 ± 2.7%, while the viability was more than 90%. The steroidogenic capacity of Leydig cells (estimated by dose-dependent stimulation with hCG) and the activity of steroidogenic enzymes (estimated by incubating cells with increasing concentrations of steroid substrates), were in line with those previously published by others (Akinbami et al, 1994) as well as our group (Andric et al, 2007(Andric et al, , 2010aKostic et al, 2008Kostic et al, , 2010Kostic et al, , 2011. These data were not showed and served to us just as internal control.…”
Section: Extraction Of Steroids From Testicular Tissuesupporting
confidence: 88%
“…Primary culture of testes were prepared as described before by our group (Kostic et al, 2010). Briefly, after TIF collection, a small part of each testis, from control and Doxa-treated groups, was quickly cut, immediately frozen at À80°C for steroid extraction and kept until extraction process (please see below).…”
Section: Primary Testicular Culturementioning
confidence: 99%
See 3 more Smart Citations